Green synthesis of silver nanoparticles from Azadirachta indica and ocimum sanctum and their antimicrobial efficacy - M. PANDIMA DEVI (International Journal of Pharma and Bio Sciences, 2016)
Nanoparticles are used immensely due to its small size and physical properties which are reportedly shown to change the performance of any other material which is in contact with these tiny particles. These particles can be prepared easily by different chemical, physical and biological approaches. But the biological method is the most efficient approach for the preparation of nanoparticles because it is eco - friendly and less time consuming. The leaves extracts of Azadirachta indica and Ocimum sanctum acts as a capping agent, reducing agents, and posses antibacterial activities and healing properties. In this study, simple and rapid approach was applied for the green synthesis of silver nanoparticles from Azadirachta indica(neem) and Ocimum sanctum (Tulsi) leaves extracts. The biosynthesized silver nanoparticles were characterized using UV – Visible Spectroscopy, XRD, and SEM. The size of biosynthesized silver nanoparticles was found to be within the range of 20-60 nm. To identify the compounds for the reduction of silver ions, the functional groups present in plant extract were investigated by FTIR. The nanoparticles were tested for their antibacterial potential against drug – resistant bacteria, Staphylococcus aureus, Pseudomonas aeruginosa, Acinetobacter baumannii and against pathogenic fungus, Rhizopus oryzae, and Aspergillus Niger. It was found that the biosynthesized nanoparticles had an inhibitory effect towards these microbes. The toxicity analysis of silver nanoparticles was determined by treating the Moong seeds (V. radiata) with different concentrations of silver nanoparticles. The results showed that 25% of silver nanoparticles solution had the better effect towards the seed germination and oxidative stress enzyme activity.